Exploring targeted therapy in retinal vasculopathy with cerebral leukoencephalopathy: a case report and review of literature - Tato-Moreno, Patricia; Lavilla Olleros, Cristina; Balastegui Martín, Héctor; Barrientos Guerrero, María; Mensa-Vilaro, Anna; Durán-García, María Esther; Sánchez-Mateos, Paloma; García-Martínez, Elena (Frontiers in Immunology, 2026)
Retinal vasculopathy with cerebral leukoencephalopathy and systemic manifestations (RVCL-S) is a rare autosomal dominant microvascular disorder caused by C-terminal truncating mutations in TREX1 gene, which impair protein localization and lead to multisystem involvement. We report a patient carrying the pathogenic TREX1 variant NM_033629.6:c.703dup (p.Val235fs), the most frequently described mutation in RVCL-S, whose clinical course was consistent with the classic phenotype but with simultaneous pulmonary granulomatous lesions compatible with sarcoidosis. Transcriptomic analysis in both the patient and his pre-asymptomatic daughter, who carries the same variant, revealed a similarly mild upregulation of inflammatory signaling pathways. Treatment with a Janus kinase inhibitor in the patient was followed by transient clinical stabilization before subsequent progression. This case expands the phenotypic spectrum of RVCL-S and underscores the importance of systematic immunological monitoring and clinical surveillance to support future development of timely strategies in asymptomatic carriers.